Évaluation d’adaptabilité de quelques génotypes d’orge (Hordeum vulgare (L.)) dans l’écologie du sud-ouest de la République Démocratique du Congo - Marcelin Lukeka Kalamo; Antoine Mumba Djamba; Vicky Nzeu Ndaya; Broline Amuri Mumbumbu; George Bouwe Nasona; Bruno Mbukula Munzemba; Amand Mbuya Kankolongo, (Revue Internationale de la Recherche Scientifique (Revue-IRS), 2025)
The objective of this study was to evaluate the adaptability of six barley genotypes under the edapho-climatic conditions of Mbanza Ngungu territory located in Kongo Central province. The tested genotypes, all originating from Germany, were experimented in two distinct sites: Kiazi and Mvuazi Research Center. The experiment was conducted according to a Randomized Complete Block design, comprising six treatments (the different barley genotypes) and three replicates. The results obtained showed significant differences between the tested genotypes. In terms of yield, the Fortune variety stood out with the highest values for both sites. Conversely, the lowest yields were observed for the Semper 10 and Danielle genotypes at both sites. Regarding plant height, the Semper 9 genotype recorded the tallest plants in Kiazi, while the Esma genotype dominated at the Mvuazi Research Center. In terms of number of spikes per square meter, the Fortune genotype performed best, while the Semper 9 genotype had the lowest results. For the thousand-grain weight, results varied according to site. At the Mvuazi Research Center, the Grace genotype had the lowest weight, while the Esma genotype had the highest weight. In Kiazi, the Ibyt923 genotype recorded the highest thousand-grain weight, while the Semper 9 variety had the lowest weight.